Egg freezing, fertility and reproductive choice : negotiating responsibility, hope and modern motherhood - Baldwin, Kylie (Emerald studies in reproduction, culture and society., 2019)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online.Growing numbers of women around the world are now accessing social egg freezing: a fertility extension technology which is enabling some women to extend their fertility and reproductive timelines when faced with age-related fertility decline. This book explores the accounts and experiences of some of the pioneering users of this technology in the UK and the USA.Drawing on theories and concepts across medical sociology and parenting culture studies, as well as literature from demography, anthropology, law, and bioethics, this book examines women's motivations and experiences of social egg freezing in the context of debates surrounding reproductive choice and delayed motherhood. The book also delves into the broader sociological questions raised by this technology in relation to the gendered burden of appropriately timed parenthood, the medicalisation of women's bodies in the reproductive domain and the further entrenchment of the geneticisation of society. It also considers the sexual politics underpinning the timing of parenthood, relationship formation and progression, and the way in which reproductive and parenting ideals, values and expectations can come in to conflict with the biological and relational realities of women's lives.